2015
DOI: 10.1371/journal.pone.0136170
|View full text |Cite
|
Sign up to set email alerts
|

The Peanut (Arachis hypogaea L.) Gene AhLPAT2 Increases the Lipid Content of Transgenic Arabidopsis Seeds

Abstract: Lysophosphatidic acid acyltransferase (LPAT), which converts lysophosphatidic acid (LPA) to phosphatidic acid (PA), catalyzes the addition of fatty acyl moieties to the sn-2 position of the LPA glycerol backbone in triacylglycerol (TAG) biosynthesis. We recently reported the cloning and temporal-spatial expression of a peanut (Arachis hypogaea) AhLPAT2gene, showing that an increase in AhLPAT2 transcript levels was closely correlated with an increase in seed oil levels. However, the function of the enzyme encod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 89 publications
1
11
0
Order By: Relevance
“…Increased gene expression was especially pronounced for acetyl-CoA carboxylase (NtACC) and enoyl-ACP reductase (NtER) ( Figure 11 ), which encode the rate-limiting step and another important early step in FA biosynthesis, respectively ( Slabas and Fawcett, 1992 ; O’Hara et al, 2007 ). Overall, our results were similar to those recently described by Chen et al (2015) , who overexpressed peanut LPAT2, another important Kennedy pathway enzyme, in transgenic Arabidopsis.…”
Section: Discussionsupporting
confidence: 92%
“…Increased gene expression was especially pronounced for acetyl-CoA carboxylase (NtACC) and enoyl-ACP reductase (NtER) ( Figure 11 ), which encode the rate-limiting step and another important early step in FA biosynthesis, respectively ( Slabas and Fawcett, 1992 ; O’Hara et al, 2007 ). Overall, our results were similar to those recently described by Chen et al (2015) , who overexpressed peanut LPAT2, another important Kennedy pathway enzyme, in transgenic Arabidopsis.…”
Section: Discussionsupporting
confidence: 92%
“…However, lipid synthesis in plants is a complicated biological process involving multiple genes, and exploring the key functional genes involved in peanut oil accumulation is important for both theoretical and practical applications. There have been some reports of the functional genes involved in TAG biosynthesis in peanut, including GPAT9, LPAAT and DGAT [39][40][41][42] . For example, the gene expression level of AhLPAAT in high-oil cultivar was found to be much higher than that in low-oil cultivar during seed development, and overexpression of AhLPAT2 in Arabidopsis increased the seed oil content of the transgenic plants and the transcript levels of several key genes related to TAG assembly 40 .…”
mentioning
confidence: 99%
“…There have been some reports of the functional genes involved in TAG biosynthesis in peanut, including GPAT9, LPAAT and DGAT [39][40][41][42] . For example, the gene expression level of AhLPAAT in high-oil cultivar was found to be much higher than that in low-oil cultivar during seed development, and overexpression of AhLPAT2 in Arabidopsis increased the seed oil content of the transgenic plants and the transcript levels of several key genes related to TAG assembly 40 . In a previous study, a GPAT9 gene was isolated from peanut and shown to be highly expressed in stems, flowers and seeds; the maximum transcript accumulation of the AhGPAT9 gene was observed at 50 DAP in the peanut cultivar Huayu19, and no GPAT genes involved in seed oil accumulation have been identified so far 39 .…”
mentioning
confidence: 99%
“…In addition, the result that PrLPAAT4 overexpression in Arabidopsis resulted in the improvement in the total FAs content ( Figure 6 e) is consistent with the findings from many previous reports. Overexpression of peanut AhLPAAT2 in Arabidopsis, the total FA content of the seeds significant increased [ 46 ]. The total FAs content is increased in the PrLPAAT1 -overexpressing Arabidopsis plants [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The same result was found in transgenic Arabidopsis overexpressing AhLPAT2 from A . hypogaea [ 46 ]. Nevertheless, the molecular mechanism of the result remains unknown and need further studies.…”
Section: Discussionmentioning
confidence: 99%